Hydrology-Shaped Plant Communities: Diversity and Ecological Function (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Aquatic ecosystems and the water they hold have attracted people over the centuries. With the technological development and increasing needs of human society, the attitude to water and aquatic ecosystems has changed. Consequently, biodiversity of freshwater ecosystems has declined dramatically and it is still decreasing. Anthropogenic exploitation of these ecosystems and alterations of their hydrology has largely influenced hydrology-shaped plant communities. This Special Issue, “Hydrology-Shaped Plant Communities: Diversity and Ecological Function” brings new outcomes about the interactions between hydrological factors and wide spectrum of plant communities. In ecosystems, where human activities directly or indirectly affected the hydrological factors, dependent plant communities have also changed or even disappeared. These plant communities have multiple ecological functions, and one of the most important are the maintenance of water quality and enhancement of local and regional diversity of other biotic communities like diatoms, invertebrates or fish. Thus, detailed knowledge and suitable management of hydrology-shaped plant communities is a prerequisite for their unconstrained ecological functions and high diversity of aquatic ecosystems in the widest sense. The Special Issue consists of ten peer-reviewed papers on plant communities in a variety of ecosystems - from the small kettle-holes in the lowlands of northern Germany to the river Danube - the largest river within the European Union, and from different wetland types in Central Europe to the Donggting Lake – fourth largest lake in China.